The ontogeny of sleep-wake cycles in zebrafish: a comparison to humans - Sorribes, Amanda; Þorsteinsson, Haraldur; Arnardóttir, Hrönn; Jóhannesdóttir, Ingibjörg H.; Sigurgeirsson, Benjamín; De Polavieja, Gonzalo G.; Karlsson, Karl Æ. (Frontiers in Neural Circuits, 2013)
Zebrafish (Danio rerio) are used extensively in sleep research; both to further understanding of sleep in general and also as a model of human sleep. To date, sleep studies have been performed in larval and adult zebrafish but no efforts have been made to document the ontogeny of zebrafish sleep-wake cycles. Because sleep differs across phylogeny and ontogeny it is important to validate the use of zebrafish in elucidating the neural substrates of sleep. Here we describe the development of sleep and wake across the zebrafish lifespan and how it compares to humans. We find power-law distributions to best fit wake-bout data but demonstrate that exponential distributions, previously used to describe sleep bout distributions, fail to adequately account for the data in either species. Regardless, the data reveal remarkable similarities in the ontogeny of sleep cycles in zebrafish and humans. Moreover, as seen in other organisms, zebrafish sleep levels are highest early in ontogeny and sleep and wake bouts gradually consolidate to form the adult sleep pattern. Finally, sleep percentage, bout duration, bout number and sleep fragmentation are shown to allow for meaningful comparisons between zebrafish and human sleep.